NEGARA LATOA: TINJAUAN BERNEGARA MASYARAKAT BUGIS DALAM LONTARA LATOA - Muqsith, Awal; Tajuddin, Muhammad Saleh; Aderus, Andi (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2020)
This study explored the concept of state in Lontara Latoa, which was used as a political reference in the kingdom of Bone since the Seventh Bone King La Tenrirawe Bongkangnge then became a political book in the land of Bugis. The concept of the state which was used as a theoretical reference was an institution of power that has a government apparatus, people, and zones or areas of power. These three elements would serve as theoretical instruments for sorting Latoa texts that talk about these three things. This research method was qualitative with the type of literature because the object of study studied was Latoa Lontara text. The data source of this research was Lontara Latoa collected by B.F. Matthes which was still written in Lontara script. The results of this study provided a state construct in the paradigm of the Bugis community as outlined in Lontara Latoa.